If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(12x+20)+10=20x-8
We simplify the equation to the form, which is simple to understand
-4(12x+20)+10=20x-8
Reorder the terms in parentheses
+(-48x-80)+10=20x-8
Remove unnecessary parentheses
-48x-80+10=+20x-8
We move all terms containing x to the left and all other terms to the right.
-48x-20x=-8+80-10
We simplify left and right side of the equation.
-68x=+62
We divide both sides of the equation by -68 to get x.
x=-0.91176470588235
| 5*(3a+2)= | | -4.4(12x+20)+10=20x-2 | | -4.5(12x+20)+10=20x-2 | | -5(12x+20)+10=20x-2 | | -6(12x+20)+10=20x-2 | | -4(12x+20)+10=20x-2 | | -2(12x+97)+10=20x-2 | | -2(12x+98)+10=20x-2 | | -2x^2-6x+1=0 | | -2(12x+98)10=20x-2 | | 9x^4-x^2-9x^2y^2+y^2=0 | | -2(12x+38)+10=20x-2 | | -2(12x+28)+10=20x-2 | | -2(12x+27.5)+10=20x-2 | | -2(12x+26.5)+10=20x-2 | | x*1.4=12 | | -2(12x+26)+10=20x-2 | | -2(12x+27)+10=20x-2 | | -2(12x+17)+10=20x-2 | | -2(12x+6)+10=20x-2 | | -2(12x+6)+10=10x-2 | | -2(12x+6)+17=10x-2 | | -2(4x+6)+17=10x-2 | | -3(4x+6)+17=10x-2 | | 0.03/12 | | 3(4x+6)+17=10x-2 | | 3(-4x+6)+17=10x-2 | | 3(-4x+6)+17=5x-2 | | 3k-K= | | 16+3y=31-2y | | r=6k-s | | 10b+3=20 |